2012
DOI: 10.1021/ja305822e
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Balloon: Expansion of a Molecular Gyrotop Cage Due to Rotation of the Phenylene Rotor

Abstract: A macrocage molecule with a bridged phenylene rotor has been reported as a molecular gyrotop, because the rotor can rotate even in a crystalline state. Although the most stable cage structure of the molecular gyrotop in a crystal was folded and shrunken at low temperature, expansion of the cage was observed at high temperature due to rapid rotation of the phenylene in a crystal. This phenomenon is analogous to the deflation and inflation of a balloon. Moreover, the unusually large thermal expansion coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 29 publications
0
37
0
1
Order By: Relevance
“…Some conceptually related synthetic efforts from other research groups merit note. Setaka and co‐workers have shown that threefold intramolecular olefin metatheses can be effected with several aromatic systems that bear para ‐substituents of the formula Si((CH 2 ) m CHCH 2 ) 3 16c. e A representative sequence leading to the gyroscope‐like bis(silane) 21 , which features a p ‐phenylene rotator and 20‐membered macrocycles, is shown in Scheme (top).…”
Section: Discussionmentioning
confidence: 99%
“…Some conceptually related synthetic efforts from other research groups merit note. Setaka and co‐workers have shown that threefold intramolecular olefin metatheses can be effected with several aromatic systems that bear para ‐substituents of the formula Si((CH 2 ) m CHCH 2 ) 3 16c. e A representative sequence leading to the gyroscope‐like bis(silane) 21 , which features a p ‐phenylene rotator and 20‐membered macrocycles, is shown in Scheme (top).…”
Section: Discussionmentioning
confidence: 99%
“…Such rotation demonstrates promise as a new class of mechanical switches, compasses, and gyroscopes. [189][190][191][192][193] When the rotor units contain an electric dipole, amphidynamic crystals may also provide an avenue for tunable dielectrics. [194][195][196] Solid-state NMR techniques are useful characterization methods to determine molecular order and the gyroscopic dynamics within amphidynamic crystals when rotors contain atoms that occupy multiple magnetically non-equivalent sites.…”
Section: Acs Nanomentioning
confidence: 99%
“…The design of molecular machines with applications in the macroscopic world remains a major challenge . We and others have addressed it by exploring the emergent properties of amphidynamic crystals, which are built with a combination of lattice forming elements and moving parts . To date, examples have been reported of amphidynamic crystals with the potential of controlling gas adsorption and desorption, electric, optic, shape memory, and luminescence, among other properties …”
Section: Figurementioning
confidence: 99%